Lost in translation? Comprehension of care for English-speaking vs. Spanish-speaking trauma patients - Allison E Berndtson (Trauma Surgery & Acute Care Open, 2025)
Background Culturally responsive care is a core recommendation to reduce health disparities. Language barriers contribute to misunderstandings, dissatisfaction, and worse outcomes. This is exacerbated in trauma when communication is constrained by time, complexity, and competing priorities. We hypothesized that Spanish-speaking trauma patients (SSP) would have less accurate comprehension of care (CC) and discharge instructions compared with English-speaking patients (ENG).Methods We retrospectively reviewed discharges from a level 1 trauma center (October 2021 to March 2022) who were aged ≥18, primarily ENG or SSP, discharge Glasgow Coma Scale score ≥14, and without memory loss. Patients were surveyed <48 hours from discharge to assess CC. Patients self-rated CC on a Likert scale and answered open-ended questions on CC and discharge instructions. Charts were reviewed to assess and rate concordance of CC with actual care and ENG and SSP cohorts compared.Results We included 46 patients (21 SSP, 25 ENG). Mean age was 48.3 years SSP, 43.3 years ENG; 47% SSP were female versus 32% ENG (p=0.28). 56% SSP had ≥high school diploma versus 72% ENG (p=0.34). Self-rated CC was similar, with both groups rating high understanding of their care and follow-up. SSP were less likely to accurately report diagnoses, home medications, and follow-up appointments than ENG. When corrected for health literacy, differences remained between groups in accuracy of diagnoses despite having high confidence in their CC.Conclusions Though both SSP and ENG self-rated their comprehension of their care highly, there were significant differences between groups’ accuracy. Increased use of certified medical interpreters throughout hospitalization may improve language disparities in patient comprehension.Level of evidence Therapeutic/care management, level IV.